Isolation and Characterization of Cinnamaldehyde Contained in Stem Barkof Cinanamon (Cinnamomumburmannii) - Yublina O. Gelang; Theo da Cunha; Luther Kadang (Journal of Applied Chemical Science, 2012)
The research about isolation and characterization of cinnamaldehyde compund that implied in skin steam of cinnamon (Cinnamomum burmannii) was done. Isolation method that used in this research is steam distillation. Cinnamon oil that result from steam skin of cinnamon in this research was 1,2 g (0,012 %). Cinnamon oil then isollated with slim chromatographic method using eluen-n hexane and ethanol with comparison 9:1, 7:3, and 1:1. Characterization cinnamon oil using Infrared spectrophotometer (IR) analysis and Gas Chromatographic- Mass Spectrophotometer (GC-MS). The analyzed result of Infrared spectrophotometer (IR) is giving absorbtion at range 1730,03 cm-1 that be character of aldehida as basic design cinnamaldehyde, while the result of GC analyzed is getting cinamaldehyde concentration 2,37%.